Achieving Insan Kamil Through Maqamat Tauhid Muhammad Nafis Al-Banjari andits Relevance to Modern Life - Muhammad Haikal As-Shidqi; Qasir Abbas (Jurnal Studi Agama, 2022)
Insan kamil is an urgent concept to be understood and imitated for humans who want to achieve human perfection and even make it a way of life. However, there are various paradigms that differ in understanding and achieving the degree of insan kamil itself. This study aims to explain a method or method in achieving the degree of insan kamil through the maqamat of monotheism of Muhammad Nafis al-Banjari, which is contained in the book of ad-Durrun Nafis. This study uses a qualitative model with the type of literature study research with content analysis methods. The results of this study indicate that people who have undergone maqamat-maqamat tauhid will arrive at fanna fillah and baqa fillah where, when a servant has achieved it, will be classified as a perfect human being. This study concludes that the concept of insan kamil is very important to understand, because in reaching the insan kamil a salik will go through the stations of monotheism where the fruit of doing this will be able to see the essence of all events in this universe to avoid actions. the bad one.